A Study of Traffic Congestion Influenced by the Pattern of Land Use. Issue 1 (1st May 2022) - Yap, J Y; Omar, N; Ismail, I
Abstract: Traffic congestion has contributed to economic loss and increased the number of traffic accidents. Previous studies have revealed that the land use pattern in Kuala Lumpur is dispersed and leads to traffic congestion. Thus, this study is to investigate the type of land use that affect the traffic congestion in Kuala Lumpur. The data in this study was collected by using 384 design questionnaires and analysed by using descriptive analysis. The results showed that the high proportion of commercial land use causes the highest level of traffic congestion. This study makes contributions as a reference for the students to gain knowledge on how traffic congestion is influenced by the land use pattern and appropriate land use planning such as mixed-land use or grid plan are important to reduce traffic congestion.